Design and Study of Distribution Map of a General Architecture for Wireless Sensor Networks Based on GDI - Guiling Sun; Wenhe Yue; Bo Liu; Weixiang Li (2008 International Conference on Computer Science and Software Engineering : 12-14 December 2008, 2008)
Based on the C# language, two-dimensional distribution map of Wireless Sensor Network (WSN) in multi-dimensional and multi-parameter fiber Bragg gratings is drawn in terms of GDI+ graphic programming technology where is ingeniously incorporated representation method of electronic maps, and achieves good effect as a perfect combination between delicacy and efficiency on account of its ability of multi-direction and multi-angle observation as well as visional and vivid characteristics. For sensor nodes data, the two-dimensional distribution map is capable of on-line real-time transmission, storage, display, judgment, alarm and so on, and then well reflects structures and conditions of sensor network. The analysis software of the WSN realizes generality, flexibility and portability, and promises widespread application.